Profiling of nosocomial infection in hepatic patients - fatma khalil; Tawfik Abed El motaleb; Mervat Abed El-kareem; Islam Elsheikh; Enas Ghoneim (Microbes and Infectious Diseases, 2022)
Background: Nosocomial infection (NCI) is a problem with global concern due to increasing morbidity and mortality in hospitalized patients. Chronic liver disease increases the chance of NCI by suppressing cell and antibody mediated immunity. Aim: We aimed in this study to visualize the problem of NCI in hepatic patients regarding organisms causing it, pattern of resistance and possible device associated with its existence. Methods: End stage chronic hepatitis C patients who admitted to the National Liver Institute Hospital, Menoufia University, were enrolled in this observational study. Different samples from alleged sites further processed by conventional culture and sensitivity techniques and confirmed by VITEK2C2 system. Antibiotic resistance pattern of isolates was assessed.  Pan drug resistance  (PDR) Acinetobacter baumannii to Omp A, bap, and Csu E virulence genes was further processed by Multiplex PCR.  Results: Gram- negative pathogens were significantly higher in CAUTI. The most predominant nosocomial organism was Pseudomonas aeruginosa which represent 19% (32 from 168), followed by Staph aureus that account for 17.86% (30 from 168), Acinetobacter baumannii signify 14.2%, Klebsiella pneumonia form 11.9%. MDR represents 123 isolates from 168 with 73.2% percentage, while XDR represents 23.8% of total isolates.  Pan drug resistance Acinetobacter baumannii represents 5 from 24 isolates. It was associated with CAUTI and CLBSI but non-significant. 4 PDR isolates show Prescence of Omp A, Csu E, and bap biofilm forming genes. Conclusions: MDR NCI in hepatic patients need more attention regarding rational use of antibiotics especially with appearance of PDR Acinetobacter baumannii carrying Omp A, Csu E, and bap biofilm forming genes.